Blood granulocyte patterns as predictors of asthma phenotypes in adults from the EGEA study. Issue 4 (4th August 2016) - Nadif, Rachel; Siroux, Valérie; Boudier, Anne; le Moual, Nicole; Just, Jocelyne; Gormand, Frederic; Pison, Christophe; Matran, Regis; Pin, Isabelle
To what extent blood granulocyte patterns may predict asthma control remains under-studied. Our aim was to study associations between blood neutrophilia and eosinophilia and asthma control outcomes in adults. Analyses were conducted in 474 asthmatics from the first follow-up of the Epidemiological Study on the Genetics and Environment of Asthma (EGEA2), including 242 asthmatics who were adults a decade earlier (EGEA1). At EGEA2, asthma control was assessed using the Global Initiative for Asthma definition (2015), and asthma exacerbations by use of urgent care or courses of oral corticosteroids in the past year. Blood EOS lo /EOS hi was defined as </≥250 eosinophils·mm −3, respectively, and NEU lo /NEU hi as </≥5000 neutrophils·mm −3, respectively. Estimates were adjusted for age, sex and smoking. At EGEA2, NEU hi was associated with asthma exacerbations and poor asthma control (OR >2.10). EOS hi was associated with higher bronchial hyperresponsiveness (BHR) (OR (95% CI) 2.21 (1.24–3.97)), poor lung function (p=0.02) and higher total IgE level (p=0.002). Almost 50% of asthmatics had a persistent pattern between surveys. Persistent NEU hi was associated with poor asthma control at EGEA2 (OR (95% CI) 3.09 (1.18–7.05)). EOS hi at EGEA1 and persistent EOS hi were associated with higher BHR (OR (95% CI) 2.36 (1.10–5.07) and 3.85 (1.11–13.34), respectively), poor lung function (p<0.06) and higher immunoglobulin E level (p<10 −4 ) at EGEA2. Granulocyte patterns were differently associated with asthma outcomes, suggesting specific roles for each one, which could be tested as predictive signatures. Blood eosinophils and neutrophils to help identify adults with subsequent risk of asthma burden http://ow.ly/A9KS301n0YR